Intervenciones de enfermería en pacientes sometidos a exéresis tumoral por tumor cerebral. una revisión sistemática de la bibliografía - Tacuri Herrera, Brayan Alexander (2026)
Nursing care carries a great responsibility, the severity of the patient, the complexity of the procedure and complications, which is intended to guide nursing interventions that improve the care process and influence to reduce complications. Objective: To design a guide of nursing interventions in the perioperative care of patients undergoing brain tumor surgery by means of a systematic review of the bibliography. Method: It is research with qualitative application, with analytical - synthetic method, with the purpose of analyzing and acquiring knowledge of nursing interventions, using PRISMA methodology, performing a systematic search in reliable databases such as: Scielo, PubMed, Scopus and academic Google, in which 98 articles were found, which through the inclusion and exclusion criteria, 10 valid articles were selected to support the research. Results: The research was able to corroborate that preoperative care, the main Nanda diagnosis is Anxiety, transoperative care the main Nanda diagnosis is Risk of ineffective perfusion of brain tissue and postoperative nursing care the main Nanda diagnosis is Acute Confusion. The nursing plan has a great impact on patients undergoing the surgical process, as they prevent complications and are responsible for contributing to their recovery.